Assessment of the knowledge, attitudes and practices on the management of biomedical waste among health care workers in Traghin City Public Hospital: Running title: Awareness and behavior of healthcare workers regarding biomedical waste management at Traghin General Hospital. (Journal of Medical Sciences, 2025)
Biomedical waste management (BMWM) is critical for public health and environmental protection, especially in resource-limited countries like Libya, where gaps in awareness and practices increase risks. This study evaluated awareness and behaviors related to BMWM among healthcare workers at Traghen General Hospital, aiming to identify areas for improvement. Using a descriptive cross-sectional design, a structured questionnaire was distributed to 200 healthcare workers, with 173 completed responses collected over five months. The questionnaire included demographic details, awareness assessment, and behavioral practices in handling biomedical waste.The findings highlighted significant gaps in awareness, as only 43.9% of participants acknowledged the increased risk of infectious diseases due to improper waste management. Notably, 90.75% emphasized integrating BMWM into academic curricula to address these gaps. Behaviorally, 90.18% of respondents adhered to proper procedures for disposing of sharp waste, while practices related to daily waste management showed lower compliance.The study highlights the urgent need for targeted interventions, such as mandatory training programs to enhance healthcare workers' knowledge and skills. Additionally, ensuring adequate infrastructure and resources are essential to support proper BMWM practices. These measures are crucial for fostering a safe healthcare environment and mitigating the health and environmental risks associated with improper waste disposal.